On the Hungarian Vocational Education System – opportunities in practical training - Boros, Zsolt (International Journal of Engineering and Management Sciences, 2019)
The system of Vocational Education in Hungary is a rather complicated and the teaching staff and the students often do not know their way around it. In a new series of articles we intend to introduce the different parts of the national vocational training system. This is the first article of the series where we summarize the ways of practical training in the Hungarian Vocational Education System.